The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijms20246313
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin Upregulates Long Non-Coding RNA MEG3 by Affecting PABPC1 in Diabetic Retinopathy

Abstract: The aim of the study was to demonstrate how transthyretin (TTR) could affect long non-coding RNA (lncRNA) of maternally expressed gene 3 (MEG3) and play important roles in diabetic retinopathy (DR). A DR model in C57BL/6 mice was established after intraperitoneal injection of streptozotocin (STZ). After intravitreal injection with TTR pAAV vector, MEG3 short hairpin RNA (shRNA), scrambled shRNA, or MEG3, retinal imaging, retinal trypsin digestion, and fundus vascular permeability tests were performed. Cell cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 40 publications
(74 reference statements)
1
41
0
Order By: Relevance
“…In vitro studies suggested that both wild-type TTR and variant TTR regulate endothelial cell functions [61,62]. Studies of microangiopathy associated with diabetes mellitus have also provided evidence regarding the regulation of endothelial cell functions by TTR [63,64]. A study of sural nerve biopsy specimens from patients with ATTRv amyloidosis demonstrated that abnormalities of endoneurial microvessels, including the disruption of blood-nerve barriers, occurred before the initiation of amyloid deposition [51].…”
Section: Possible Impact Of Nonfibrillar Ttrmentioning
confidence: 99%
“…In vitro studies suggested that both wild-type TTR and variant TTR regulate endothelial cell functions [61,62]. Studies of microangiopathy associated with diabetes mellitus have also provided evidence regarding the regulation of endothelial cell functions by TTR [63,64]. A study of sural nerve biopsy specimens from patients with ATTRv amyloidosis demonstrated that abnormalities of endoneurial microvessels, including the disruption of blood-nerve barriers, occurred before the initiation of amyloid deposition [51].…”
Section: Possible Impact Of Nonfibrillar Ttrmentioning
confidence: 99%
“…Under hyperglycemic conditions, TTR represses angiogenesis by inhibiting the proliferation of hRECs through the tyrosine protein kinase receptor 2 (Tie 2) signaling pathway [ 240 ]. TTR also suppresses the proliferation of hRECs by long noncoding RNA (lncRNA) MEG3 in the miR-223-3p/FBXW7/Notch1 signaling pathway [ 225 , 241 ]. Therefore, TTR regulates lncRNAs to repress vascular leakage in the retina [ 226 , 241 ].…”
Section: Ttr Regulation Of Angiogenesismentioning
confidence: 99%
“…TTR also suppresses the proliferation of hRECs by long noncoding RNA (lncRNA) MEG3 in the miR-223-3p/FBXW7/Notch1 signaling pathway [ 225 , 241 ]. Therefore, TTR regulates lncRNAs to repress vascular leakage in the retina [ 226 , 241 ]. TTR is also able to regulate and interact with vascular endothelial growth factor [ 240 , 242 ].…”
Section: Ttr Regulation Of Angiogenesismentioning
confidence: 99%
“…ShRNA were administrated with previous study (Fan et al, 2019), mice in DM+sh-NEAT1 group were injected with 1 µL of shRNA targeting NEAT1 in the vitreous cavity, and mice in DM+sh-NC group were injected with the same amount of non-targeting shRNA. Mice were injected every three weeks.…”
Section: Diabetic Mice Modelmentioning
confidence: 99%
“…Many genetic variants found by genome-wide association studies (GWAS) increased the possibility of type 2 diabetes (Flannick & Florez, 2016), such as sex-determining region Y-related (SRY) high-mobility group box 4 (SOX4), which was discovered as a diabetes susceptibility gene and a new-called master regulator of EMT (Ragvin et al, 2010). It was reported that inhibition of SOX4 could decrease the expression of EMT-related mRNA expression and protein levels in human peritoneal mesothelial cells (HPMCs) induced with TGF-β1 (Xiao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%